PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. SGI - Chusnah, Chusnah; Purwanti, Heni (Kinerja, 2019)
In this study, the authors took the title "The Effect of Work Discipline and Motivation on employee performance on PT. SGI ". The purpose of this study was to determine the effect of work discipline, and motivation on employee performance partially or simultaneously. Based on the results of data analysis and partial discussion of work discipline (X1) a positive and significant effect on employee performance. Motivation (X2) partially has a positive and significant effect on employee performance. Simultaneously work discipline and motivation have a positive and significant effect on employee performance. The results of the study simultaneously from the influence of work discipline and motivation on employee performance obtained 53.4% while the remaining 46.6% was influenced by other variables not included in this study